Buckling of composite cylindrical shells with ovality and thickness variation subjected to hydrostatic pressure - Zhun Li; Ke-chun Shen; Xin-hu Zhang; Guang Pan (Defence Technology, 2022)
The initial geometric imperfection is one of the primary factors affecting the buckling behaviors of composite cylindrical shells under hydrostatic pressure. In this study, ovality and thickness variations as two representative types of the geometric imperfections are considered. After measuring the geometric imperfections, a typical carbon fiber reinforced polymers (CFRP) cylindrical shell is tested to obtain the buckling pressure. The buckling behaviors of the shell sample are analyzed in combination with the strain responses. By using the nonlinear numerical analysis, the buckling shapes of the CFRP cylinder shells with different combinations of ovality and thickness variation are firstly discussed. The rules of influence of such imperfections on the buckling pressure are then obtained by nonlinear regression method. Finally, an empirical formula is proposed to predict the buckling pressure of the composite cylinder shells, and the calculated results from the formula are in good agreement with the numerical results.